Responses of soil microbial respiration to plantations depend on soil properties in subtropical China - Yan-jie ZHANG; Yue YAN; Xiang-ping FU; Jie YANG; Su-yan ZHANG; Shan XU; Zheng TANG; Zhong-fang LI; Shun-bao LU (Journal of Integrative Agriculture, 2016)
Assessing the impact of plantation on microbial respiration (MR) is vitally important to understand the interactions between belowground metabolism and land use change. In this study, cumulative MR was determined by alkali absorption method in 1, 3, 7, 14, 21, 28, 35, 42, 49, and 56 days from the soil in a representative plantations in the subtropical region of China. The treatment of plantations contained no plant (CK), orange trees (Citrus reticulata)+Bahia grass (Paspalum notatum) (GB), orange trees (C. reticulata)+Bahia grass (P. notatum)+soybean (Giycine max (L.) Merrill) (GBH). Results showed that plantation had significant effects on microbial respiration and the responses of microbial respiration to plantation from different soil layers and topographies were different: in 0–20 cm in uphill: GB>GBH>CK; in 20–40 cm in uphill: GBH>CK>GB; in 0–20 cm in downhill: GBH>CK>GB; in 20–40 cm in downhill: GB>CK>GBH. Furthermore, plantation also altered the relationships between MR and soil properties. In CK, microbial respiration was positively correlated with NH4+ and soil total N, and negatively correlated with soil moisture, pH, NO3−, and microbial biomass carbon (MBC). In GB, microbial respiration under GB significantly negatively correlated with dissolved organic carbon (DOC). In GBH, microbial respiration under GBH was positively correlated with NH4+, MBC, total soil carbon (TC), and total soil nitrogen (TN), and negatively correlated with soil moisture (SM), pH, NO3−, and DOC. The underlying mechanisms could be attributed to soil heterogeneity and the effects of plantation on soil properties. Our results also showed that plantation significantly increased soil C storage, which suggested plantation is a key measure to enhance soil C sequestration and mitigate global CO2 emission, especially for the soil with low initial soil carbon content or bared soil.